Effectifity and Cost Analysis of Omeprazole and Pantoprazole for Stress Related Mucosal Disease Prophylaxis in ICU - Dyah Atmi Tri Sukengtyas; Tri Murti Andayani; L. Endang Budiarti (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Currently, the most effective therapeutic agent as a Stress Related Mucosal Disease (SRMD) prophylaxis therapy is the group of Proton Pump Inhibitor (PPI). In Indonesia, PPI agent most commonly used is pantoprazole and omeprazole, for they are already available in the form of injection and also available in generic product. This study aimed to determine the effectiveness and the therapy cost of omeprazole and pantoprazole used as a prophylaxis agent of SRMD. This study used observational analytic method using a retrospective cohort study. The subjects were patients in ICU of Bethesda Hospital in Yogyakarta with age ≥ 18 year old who received the therapy of omeprazole or pantoprazole as a prophylaxis of SRMD during January 2012 – September 2016 who meet the inclusion and exclusion criteria. The effectivity of therapy was seen by the bleeding events. The cost was calculated based on the amount of fee required by the patient, both the use of the medicine as a prophylaxis therapy of SRMD and for the bleeding therapy of SRMD. The value of Expected Monetary Value (EMV) was then calculated using the method of Decision Tree. Subject in this study were 152 patients, in which there were 76 patients on each group therapy of pantoprazole and omeprazole. The comparison between the number of patients who did not experience bleeding between group of pantoprazole and group of omeprazole is 85.5%: 81.6% (p = 0.512). The value of EMV in the pantoprazole group is Rp. 431.490,76, while the omeprazole group is Rp. 382.042,57. There is no difference in the effectivity between pantoprazole and omeprazole as a prophylaxis of SRMD, and the cost for SRMD prophylaxis is cheaper in the omeprazole therapy than in the pantoprazole therapy.